You should know that you may find the slope of the line converting the equation of the function to the slope intercept form such that:

`y = mx + n`

m represents the slope of the line `y = mx + n`

Reasoning by analogy , you need to convert...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You should know that you may find the slope of the line converting the equation of the function to the slope intercept form such that:

`y = mx + n`

m represents the slope of the line `y = mx + n`

Reasoning by analogy, you need to convert the equation of the function `f(x) = -2x - 9` to the form mentioned above such that:

`y = -2x - 9`

Notice that the slope is given by the leading coefficient such that:

`m = -2`

**Hence, evaluating the slope of the given function yields `m=-` 2.**